Lowering Blood Pressure Through The Consumption Of Carrot Juice (Honey Carrot) In Hypertension Patients - Hariati .; Dewi Tiansa Barus; Riyanto . (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
The high rate of hypertension causes hypertension to be a problem that must be overcome. In herbal medicine with the therapy of giving wordu juice (honey carrots), it contains potassium which can maintain blood pressure and aceticolin which helps improve blood vessel circulation. To determine the effect of giving Wordu juice (carrots and honey) on the reduction of blood pressure in patients with hypertension. The research design used a pre-experimental design with a one group pretest-posttest design. The variables in this study were Wordu Juice (Honey Carrot) as the independent variable and hypertension sufferers as the dependent variable. The population in this study were all hypertension patients at Biru-Biru Health Center in 2021. Sampling in this study used a non-probability sampling method by accidental sampling, in which the researcher took a sample based on predetermined criteria as many as 28 respondents. Data were collected using observation sheets and tested by t test. The results of the analysis using the dependent T test in patients with hypertension can be concluded that the pretest and posttest systolic experimental group with a sample of 28 respondents had a P-value (0.001) <? 0.05, then H0 was rejected. Posttest on Hypertension Patients in the Work area of ??the Binjai Village Health Center. It is hoped that health workers can apply non-pharmacological therapies such as herbal medicine. Giving Wordu Juice to treat hypertension so that the services provided can be of higher quality and the services are carried out more precisely.